2021
DOI: 10.1136/bmj.m4785
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking research processes to strengthen co-production in low and middle income countries

Abstract: Co-production needs to become an integral part of the training and funding of researchers to ensure research meets everyone's needs, argue David Beran and colleagues on 21 February 2021 by guest. Protected by copyright.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 15 publications
3
41
0
Order By: Relevance
“…To facilitate these dialogues and to enable the reflection of societal concerns, Beran et al advocate for platforms for exchange and the institutionalisation of a multistakeholder approach. 50 Consistent with findings of previous studies, our study showed that trusted relationships can lead to trust in evidence and the acceptance and adoption of new evidence, which may otherwise be regarded as controversial or 'negative' evidence. [51][52][53] This may be the case if foundational knowledge, which has entrenched within evidence consumers over time, is being challenged, not meeting their expectations.…”
Section: Political Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…To facilitate these dialogues and to enable the reflection of societal concerns, Beran et al advocate for platforms for exchange and the institutionalisation of a multistakeholder approach. 50 Consistent with findings of previous studies, our study showed that trusted relationships can lead to trust in evidence and the acceptance and adoption of new evidence, which may otherwise be regarded as controversial or 'negative' evidence. [51][52][53] This may be the case if foundational knowledge, which has entrenched within evidence consumers over time, is being challenged, not meeting their expectations.…”
Section: Political Modelsupporting
confidence: 91%
“…To facilitate these dialogues and to enable the reflection of societal concerns, Beran et al advocate for platforms for exchange and the institutionalisation of a multistakeholder approach. 50 …”
Section: Discussionmentioning
confidence: 99%
“…Weak application validity can also arise if the research problem and questions are framed from a purely disciplinary or academic perspective (Beran et al 2021). Future archetype analyses may improve their application validity by embracing transdisciplinary co-creation of knowledge through participatory research approaches (Wuelser et al 2021, Jacobi et al 2022), as discussed in section 4.3.2.…”
Section: Directions For Future Validation 431 Improving Weaker Validity Dimensionsmentioning
confidence: 99%
“…Trust is particularly important in working with less powerful stakeholders 471314. In low and middle income countries funders and donors may need to reorient their views to place more trust in local knowledge1516; new kinds of funding from USAID and other donors have supported initiatives to build trust and facilitate co-production 15.…”
mentioning
confidence: 99%
“…Finally, a different approach to research funding will be needed to support the complex partnerships necessary for co-production. Historically, research funding was mainly provided for short term projects and did not effectively support the development of long term partnerships or collaborative infrastructure; Beran and colleagues describe the need to fund “partnerships rather than projects.”13 More recently, many agencies have established funding opportunities that support long term relationships and co-production (such as the Doris Duke Charitable Foundation’s African Health Initiative,15 Australia’s National Health and Medical Research Council partnership centres, the UK’s collaborations for leadership in applied health research and care, and Canada’s knowledge to action grants). These are to be encouraged as critical to co-production.…”
mentioning
confidence: 99%